Pendidikan Islam Dan Perubahan Sosial: Aktualisasi Nilai-Nilai Pendidikan Islam dalam Perubahan Sosial - Syahidan Syahidan (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
The religion of Islam revealed by Allah as a religion that "rahmah li al-'alamin", then Islam is revealed to give glory to all creatures that exist in this earth which is a creation from Allah swt. Islam for change in the life order of society. One of the changes is through Islamic education taught to the community at all levels, be it children, adolescents, adults or old age. Since its inception, Islamic education has undergone various developments, ranging from the era of awakening, goldenness, decline and development and education of Islam with modern education now. Social change in Muslim society is usually indicated by the development of civilization within the Muslim community. The substance of social change is the power of Muslim civilization that can bring changes in the social fabric of society